A boost for the EW SUSY hunt: monojet-like search for compressed sleptons at LHC14 with 100 fb-1 - Barr, A; Scoville, J (Springer, 2015)
Current Large Hadron Collider (LHC) analyses are blind to compressed supersymmetry (SUSY) models with sleptons near the lightest super partner (LSP) in mass: ml~−mχ~01 ≡ Δm ≲ 60 GeV. We present a search sensitive to the very compressed range 1 3 GeV < Δm < 24 GeV using the channel pp→l~+l~− + jet → l+l−χ~01χ~01+ jet with soft same-flavor leptons and one hard jet from initial state radiation (p T j > 100 GeV). The sleptons recoil against the jet boosting them and their decay products, making the leptons detectable and providing substantial missing transverse momentum. We use the kinematic variable mT2 along with a different-flavor control region to reduce the large standard model backgrounds and control systematic uncertainty. We find the analysis should allow LHC14 with 100 fb−1 to search for degenerate left-handed selectrons and smuons in the compressed region up to ml~L ≲ 150 GeV. In addition, it should be sensitive to ml~L ≲ 110 GeV for the very challenging case of auto-concealed SUSY, in which left-handed sleptons decay to the Kaluza-Klein tower of a modulino LSP which lives in d = 6 extra dimensions. In both the compressed spectrum and auto-concealed SUSY scenarios this analysis will need more data to improve on LEP2 limits for right-handed sleptons due to their smaller cross sections.